The Estimation of Foetomaternal Haemorrhage by Flowcytometry - Nurasyikin Y; Suria AA; Soon, Peng Ng; Leong, CF (Penerbit UKM, 2015)
Fetomaternal haemorrhage (FMH) may occur following a sensitizing event, during pregnancy or at delivery. In cases of rhesus (Rh) incompatibility between mother and the fetus, it can thus subject to the haemolytic disease of the newborn. The Kleihauer test for quantification of FMH lacks standardization and results are less accurate. Furthermore, it cannot differentiate the fetal cell from the adult HbF. Flowcytometry analysis using monoclonal antibodies, is a new technique for the quantification of FMH and it allows larger number of cells to be analysed. It is also able to differentiate the fetal cell from maternal HbF, and thus is more sensitive and accurate. The objective of our study was to determine the FMH using the flowcytometric analysis of anti-HbF antibody and to correlate the FMH using flow cytometry and the standard Kleihauer test. Ninety eight peripheral blood samples from pregnant women at more than 20 weeks of pregnancy and post delivery were analyzed by both methods. The percentage of the fetal cells were recorded and the FMH were calculated. We found a fair correlation between the two methods with the correlation coefficient r = 0.633 (p<0.05). The concordance rate was 66.3%. Flow cytometric method, however, gave higher values in 70.4% of cases as compared to the Kleihauer test. These could be due to the autofluoresce of contaminated white blood cell or using anti HbF which is less specific than anti-D. Other possible factors could be due to the fluorochrome used. Therefore, in order to increase the accuracy, we recommend the use of dual labeling of red cells with glycophorin A which is a marker for red cells and compare the use of monoclonal anti HbF and anti-D for analysis.